INISIASI PEMBUATAN PUPUK ORGANIK DARI SAMPAH RUMAH TANGGA SEBAGAI MEDIA TANAM DALAM PROGRAM PENANAMAN 1000 POHON - Dian Wijaya Kurniawidi; Siti Alaa; Irma Pratiwi; Marlita Yudiawati; Gaoura Valentina (Jurnal Warta Desa (JWD), 2021)
The overall development of Covid-19 has raised concerns in various sectors, including the agriculture, aquaculture, and livestock sectors. Based on the observations in Pagesangan Timur, Karang Anyar Village, especially around the Ittihadil Ummah Islamic boarding school, public awareness is still lacking in re-processing household waste by separating types of waste. Alternative Sustainable Food Homes with a program of fabrication of organic fertilizer from household waste allows the community to recycle household waste separated according to its type. The use of fertilizers produced is exemplified by planting 1000 trees. Fabrication of organic fertilizer and planting 1000 trees were carried out through direct outreach and practical methods. This organic fertilizer is obtained from the daily waste of the boarding school kitchen and fruit waste, especially bananas at the Pagesangan market, as a source of glucose. The results obtained include one tub equivalent to 50 liters of organic compost fertilizer. The application of planting 1000 trees was carried out with a sample of ten kinds of plants with ten trees each in the PP Ittihadil Ummah environment in the form of vegetables, fruit trees, and leafy and ornamental plants..